Youth engagement the civic-political lives of children and youth - Nenga, Sandi Kawecka; Taft, Jessica K. (Sociological studies of children and youth ;, 2013)
In recent years, civic and political institutions have stepped up their efforts to encourage youth participation: schools promote volunteerism, non-profits provide opportunities for service, local governments create youth councils, and social movement organizations discuss the need to encourage a new generation of activists. This volume adopts a critical approach to the civic and political socialization projects which aim to transform children and youth into upstanding citizens. By synthesizing the study of young peoples civic and political socialization under the rubric of "Youth Engagement", the interplay of the civic and the political throughout young peoples lives is considered. Chapters critically examine the multiple and contested meanings of ideal citizenship and reveal how children and youth craft active citizenship as they encounter and respond to the various institutions and organizations designed to encourage their civic and political development.